Teachers’ feelings of safeness in school-family-community partnerships: Motivations for sustainable development in moral education - Nguyen Thi Ngoc Lien; Nguyen Thi To Khuyen; Nguyen Thi Tho; Nguyen Ngan Hoa; Nguyen Thi Hanh; Chu Cam Tho; Tuong Duy Hai; Nguyen Van Bien (Institute of Advanced Engineering and Science, 2021)
This study aims to get insights into teachers' safety feelings in families, schools, and communities’ partnerships to facilitate the Vietnam context’s moral education process. We used a survey method with the instrument having 19 Likert-scale items, namely teachers' feelings of safeness in SFC partnerships (SSFC). The data from 371 Vietnamese teachers followed a simple random sampling strategy. We conduct multiple regression analyses to get insight into the relationship between four groups of variables and teachers' feelings of safeness, namely teachers’ background, collaborated actions between teachers and families, families’ mental encouragement for teachers, and collaborated actions between families and communities. These results find that the school level, collaborated actions between teachers and families, and families’ mental encouragement for teachers are statistically significant to teachers’ feelings of safety. Moreover, the variable group of collaborated actions between teachers and families records the highest positive beta value in multiple regression analyses. In other words, the improvement of collaborated actions between teachers and families is a critical motivation to leverage teachers’ feelings of safeness in SFC partnerships. These results provide valuable information for sustainable development in moral education.